A rare case of focal segmental glomerular sclerosis and subsequent necrotizing crescentic glomerulonephritis in the same patient - Jake Cho; Erika Lara; Izuchukwu Nwakoby (Society of Diabetic Nephropathy Prevention, 2019)
Background: Focal segmental glomerular sclerosis (FSGS) and necrotizing crescentic glomerulonephritis is a rare combination of diagnoses in the same patient. We report on a patient with FSGS who 10 years later developed anti-neutrophil cytoplasmic antibody (ANCA) associated glomerulonephritis. Case Presentation: Patient is a 60-year-old female with chronic kidney disease stage 3, osteopenia and anemia. In 2007, she was positive for ANCA proteinase-3 antibody, but kidney biopsy revealed FSGS. She was treated with high-dose oral steroids with tapered dose and went into remission. In 2017, she developed acute renal failure with increased proteinuria. Despite prior FSGS diagnosis, her new kidney biopsy revealed pauci-immune necrotizing glomerulonephritis. Patient was treated with methylprednisolone 250 mg IV for three days and high dose oral steroids with tapered dose. She was also started on rituximab 375 mg/m2 IV once weekly for 4 doses. Given the extent of kidney damage, the patient decided to start peritoneal dialysis and she is also on the kidney transplant list. Conclusions: The rare concurrence of FSGS and ANCA associated glomerulonephritis has not yet been reported. The case also emphasizes the significance of screening for ANCA or obtaining kidney biopsy when indicated not only as the gold standard for diagnosis but also as prognostic value.